The Effect Of Using Smart Technical English And Quizlet Applications On Enhancing Learning Interest For Students Of Anastasia Private Elementary School In Academic Year 2024/2025 - Roikestina Silaban; Tulus Januardi Tua Panjaitan; Faija Sihombing (Program Studi Pendidikan Biologi, 2025)
Increasing students' learning interest is one of the main challenges in education during the digital era. This study aims to analyze the influence of using the Smart Technical English and Quizlet applications on the learning interest of students at Anastasia Private Elementary School in the 2024/2025 academic year. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 60 students divided into experimental and control groups. Data were collected through learning interest questionnaires, interviews, and observations, and analyzed using descriptive and inferential statistical tests. The results showed that the use of Smart Technical English and Quizlet significantly improved students' learning interest compared to conventional methods. Factors such as interactivity, ease of access, and adaptive learning features in both applications contributed to creating an engaging and effective learning environment. These findings highlight the importance of integrating technology in education to enhance students' motivation at the elementary school level.